Odpowiedzi

Najlepsza Odpowiedź!
2010-02-16T15:24:54+01:00
A) -27x+1=2x+59 / -2x -1
-29x = 58 /:2
-x = 2 / * -(1)
x = -2
Spr : (-27)*(-2) + 1 = 2*(-2) + 59
54 + 1 = -4 + 59
55 = 55


b)45x-19=19x-45 / -19x
26x - 19 = -45 /+19
26x = -26
x = -1
Spr:
45*(-1) - 19 = 19* (-1) - 45
-45-19 = -19-45
-64 = -64


c)82x-9=-18x+1 /+18x
100x - 9 = 1 /+9
100x = 10
x = 10/100
x = 0,1
Spr.
82*0,1 - 9 = -18*0,1 + 1
-0,8 = -0,8


2010-02-16T15:27:49+01:00
-27x+1=2x+59
-27x-2x=59-1
-29x= 58/:-29x
x= -2



45x-19=19x-45
45x-19x=-45+19
26x=-26/26x
x=1




82x-9=-18x+1
82x+18x=1+9
100=10/:100
x= 0,1
2010-02-16T15:27:56+01:00
A) -27x+1=2x+59
-27x - 2x = 59 - 1 Spr. -29 * 2 = 58
-29x = 58 / : (-29)
x = 2

b)45x-19=19x-45
45x - 19x = -45 + 19 spr. 26 * (-1) = -26
26x = -26 / : (-26)
x= -1

c)82x-9=-18x+1
82x + 18x = 1 + 9 spr. 100 * 0,1 = 10
100x = 10 / : 100
x=0,1